The Process of Identifying Students with Special Needs in Inclusive Elementary Schools - Fadila, Tazkiya Indah; Sunardi, Sunardi (Angstrom Centre of Education, 2024)
The identification process is the first step in determining the special needs of learners. This stage is important as a basis for conducting assessments and designing individual learning programs for learners with special needs. This research uses a qualitative descriptive method. Data collection was done through classical tests, observation and interviews. The data was presented in graphical form and then analyzed descriptively. The identification results showed 2 students with special needs. The types of special needs found are specific learning difficulties including dyslexia, dysgraphia and dyscalculia.